Flood hazard mapping in convex floodplain: multiple probability models fusion, bank threshold and levees effect spatialization - Guerriero, Luigi; Cusano, Angelo; Ruzza, Giuseppe; Revellino, Paola; Guadagno, Francesco Maria (Italian journal of engineering geology and environment, 2019)
<span data-sheets-value="[null,2,"This paper presents a first attempt to model flood hazard in convex upward floodplains through the combination of multiple probability models fusion and topographic-based flood inundation models. Our procedure is optimized for convex floodplains through the adoption of a multiplicative probability threshold that simulates the effect of natural banks bounding the river course and is able to account for the presence of artificial\u000dlevees. We have applied this procedure to a segment of the lower course of the Volturno river in the Caserta Province. This area has been historically affected by flood events and since 1927 has been monitored with several hydrometric stations. We have used data from two of these stations and a LiDAR derived high-resolution topography to develop two flood hazard scenarios. The first is derived using a Generalized Extreme Value distribution, while the second is derived using a Gamma distribution function of available data. As boundary condition, we have considered a reference scenario corresponding to an estimated 500-year flood. The hazard maps provide an overview of the flood hazard in the lower sector of the Volturno river."]" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">This paper presents a first attempt to model flood hazard in convex upward floodplains through the combination of multiple probability models fusion and topographic-based flood inundation models. Our procedure is optimized for convex floodplains through the adoption of a multiplicative probability threshold that simulates the effect of natural banks bounding the river course and is able to account for the presence of artificial levees. We have applied this procedure to a segment of the lower course of the Volturno river in the Caserta Province. This area has been historically affected by flood events and since 1927 has been monitored with several hydrometric stations. We have used data from two of these stations and a LiDAR derived high-resolution topography to develop two flood hazard scenarios. The first is derived using a Generalized Extreme Value distribution, while the second is derived using a Gamma distribution function of available data. As boundary condition, we have considered a reference scenario corresponding to an estimated 500-year flood. The hazard maps provide an overview of the flood hazard in the lower sector of the Volturno river.